"Estresores y Nivel de Estrés en Madres de Recién Nacidos. Hospital Regional Docente de Trujillo. 2012" - Dávila Holguin, Esther Del Rocio (2012)
The present study is a descriptive correlational cross sectional was conducted in the Regional Teaching Hospital of Trujillo, with the purpose of determining the relationship that exist between some causes of stress: hospitalization environment, treatment applied to the new born and communication with medical staff on the level of stress of the mothers of new born hospitalized in the Neonatology Service. The sample consisted of 63 mothers who met the inclusion criteria mentioned in the investigation, for data collection were used two instruments: A Meassuring scale shows the level of stress, and the Scale of Medition of the causes of stress. The data was tabulated and presented in graphs and statistical tables of single and double entry. The analysis of the relationship between the study variables was performed by Independent Testing Criteria (Chi square). Discussing from the results we obtained the following conclusions:  The 74 percent of mothers of new borns hospitalized in the Neonatology Service showed a high level of stress and the 26 percent level medium.  The cause of stress the hospital environment have the 62 percent of level maximum and the 38 percent of minimum level, the cause of stress treatments applied to the new born have the 72 percent of maximum level and the 28 percent of miimum level, and the cause of stress communication with the medical staff have the 58 percent of maximum level and the 42 percent of minimum level.  The causes of stress: the hospital environment, treatments applied to the new born had a statistically significant relationship (p<0.05) and communication with the medical staff highly significant relationship. Key words: Stress, Level of stress, Causes of stress.